Disability as Biographical Disruption - Viluckienė, Jolita (Sociologija. Mintis ir veiksmas, 2010)
This article explores physical disability as biographical disruption caused to persons confined to a wheel-chair after the unexpected cerebral trauma or palsy. Their personal narratives based on the qualitative in-depth interviews suggest that they perceive disability as the subjective reality that shook their world to its foundations, provoked a breakdown of their everyday taken for granted word, disrupted the routine of social practices, redefined their social roles and divided their biographies into two periods: “before” the disability and “after” it. Disability, as it insinuates into biography, is perceived not only as a bodily substance, but it also transforms personal and social identity and requires, through resocialization process, to recreate the meaningful structures of the reality and provide a new valid justification for this reality. Thus, the disability becomes a significant factor that shapes the further biographical situation, as in many cases, impaired physical mobility elicits changes in lifestyle, profession and employment, attitudes to him/herself and to others as well as value orientations.